N-(1-Phenylethyl)aziridine-2-carboxylate esters in the synthesis of biologically relevant compounds - Głowacka, Iwona E.; Trocha, Aleksandra; Wróblewski, Andrzej E.; Piotrowska, Dorota G. (Beilstein Journal of Organic Chemistry, 2019)
Since Garner’s aldehyde has several drawbacks, first of all is prone to racemization, alternative three-carbon chirons would be of great value in enantioselective syntheses of natural compounds and/or drugs. This review article summarizes applications of N-(1-phenylethyl)aziridine-2-carboxylates, -carbaldehydes and -methanols in syntheses of approved drugs and potential medications as well as of natural products mostly alkaloids but also sphingoids and ceramides and their 1- and 3-deoxy analogues and several hydroxy amino acids and their precursors. Designed strategies provided new procedures to several drugs and alternative approaches to natural products and proved efficiency of a 2-substituted N-(1-phenylethyl)aziridine framework as chiron bearing a chiral auxiliary.
Keywords: alkaloids; amino acids; asymmetric synthesis; ceramides; chiral catalysis; chiral pool; N-(1-phenylethyl)aziridine chiron; sphingoids